Review of the ground beetle subgenus Micronialoe from Korea, with a description of a new species (Coleoptera: Carabidae: Pterostichus) - Kim, Dooyoung; Suh, Sang Jae (Zootaxa, 2024)
Micronialoe (Pterostichini: Pterostichus) is a poorly known subgenus of the ground beetle genus Pterostichus, which includes three species from the Korean Peninsula and adjacent islands. Here, a new species, Pterostichus (Micronialoe) spinulosus sp. nov., was identified among the specimens collected from Mt. Biseulsan and Mt. Choejeongsan, Daegu-si, Korea. Along with the description of the new species, all Korean species are redescribed, and the subgenus is re-diagnosed. The new species is morphologically allied to P. (M.) bifoveolatus, thus, the intraspecific variation of the new species is examined and valid characters for distinguishing species are discussed. A key for the identification of the species of the subgenus is also provided.